Using Community-Engaged, Arts-Based Methods to Explore Housing Insecurity in Rural-Urban Spaces - Pin, Laura; LeBlanc Haley, Tobin; Levac, Leah (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2024)
This article explores how community-engaged, arts-based research methods can enrich our understanding of homelessness, with a specific focus on housing insecurity in rural-urban communities. Drawing on a digital storytelling project in Dufferin County, Ontario, that featured twelve storytellers and eight stories, this article explores the complexities of homelessness that are often neglected in official narratives of housing and home. We argue that the dominant method of documenting homelessness—enumeration through Point-in-Time (PiT) Counts—provides a limited understanding of homelessness and contributes to the invisibility of these problems in rural-urban spaces. We explore how a participant-led, arts-based approach can point to key areas for policy change by drawing attention to housing insecurity as a form of homelessness and highlighting how individual circumstances intersect with structural factors.